Realisms in East Asian Performance - Nakamura, Jessica; Saltzman-Li, Katherine (University of Michigan Press, 2023)
Existing scholarly discussions of theatrical realism have been predominantly limited to 19th-century European and Russian theater, with little attention paid to wider explorations and alternative definitions of the practice. Examining theater forms and artists from China, Japan, and Korea, Realisms in East Asian Performance brings together a group of theater historians to reconsider realism through the performing arts of East Asia. The book's contributors emphasize trans-regional conversations and activate inter-Asian dialogues on theatrical production. Tracing historical trajectories, starting from premodern periods through today, the book seeks to understand realisms' multiple origins, forms, and cultural significances, and examines their continuities, disruptions, and divergences. In its diversity of topics, geographic locations, and time periods, Realisms in East Asian Performance aims to globalize and de-center the dominant narratives surrounding realism in theater, and revise assumptions about the spectacular and theatrical forms of Asian performance. Understanding realism as a powerful representational style, chapters collectively reevaluate acts of representation on stage not just for East Asia, but for theater and performance studies more broadly.